This preview shows page 1. Sign up to view the full content.
Unformatted text preview: c) F=(((A+B)'+C')'+D)' d) F=AB(C'+D')+A'B'C'+CD'(A+C') 3. Prove the equality of the following equations and then using the principle of duality to obtain their duals. a) AB + AB'C= AB + AC b) XY' + X'Z + Y'Z= XY' + X'Z c) (B'+C)(B'+D)=B'+CD...
View
Full
Document
This homework help was uploaded on 04/22/2008 for the course ECSE 2610 taught by Professor Ji during the Spring '08 term at Rensselaer Polytechnic Institute.
 Spring '08
 Ji

Click to edit the document details